Systemic Lupus Erythematosus: A Review - Habib , Nasrin; Pillay , Sellaiah S.; Afrose, Tahmina; Rashid , Mamunur (Innovations in Microbiology and Biotechnology Vol. 6, 2022)
Systemic lupus erythematosus (SLE) is a persistent heterogeneous autoimmune disease that affects multisystem of the body. Because systemic lupus erythematosus is a multisystem disease, it can affect any tissues, organs, or even whole systems. There are several types of lupus, including cutaneous lupus erythematosus (CLE), which affects the skin and causes a malar rash, discoid lupus erythematosus (DLE), and systemic lupus erythematosus, which affects one or more internal organs. The inflammation induced by direct antibody reactions to bodily tissues, as well as the deposition of immune complexes, cause the harm. Glucocorticoids, immunosuppressant, and anti-malarial are the combination therapy used to treat SLE besides providing counseling and awareness. Lupus erythematosus in any form particularly SLE are prevalent in women compared to men with ratio of 6:1. It affects people of all ages, but women between the ages of 20 and 45 are the most commonly affected. Lupus is an autoimmune disease characterized by acute and chronic inflammation of various tissues of the body. Autoimmune diseases are illnesses that occur when the body's tissues are attacked by its own immune system.